2020
DOI: 10.1017/s175577392000034x
|View full text |Cite
|
Sign up to set email alerts
|

Elite cueing and attitudes towards trade agreements: the case of TTIP

Abstract: How does elite communication affect citizens’ attitudes towards trade agreements? Building on a growing literature on context factors influencing public opinion about trade and trade agreements; we argue that citizens rely on cues provided by political elites, especially political parties, when forming their views towards these agreements. Such cueing effects are most likely for citizens with little information about a trade agreement and for citizens receiving cues from trusted elites. In addition, citizens e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Third, and finally, research has examined the effects of citizens taking cues from elites when making up their minds about policies and institutions at the international level. Such research has indicated that positive / negative cues communicated by trusted elites make citizens more / less favorable toward the EU (De Vries & Edwards, 2009;Gabel & Scheve, 2007;Steenbergen et al, 2007) or trade agreements (Dür & Schlipphak, 2020). Regarding international organizations, Dellmuth and Tallberg (2020a) have also demonstrated that governmental cues may influence citizens' attitudes toward the UN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Third, and finally, research has examined the effects of citizens taking cues from elites when making up their minds about policies and institutions at the international level. Such research has indicated that positive / negative cues communicated by trusted elites make citizens more / less favorable toward the EU (De Vries & Edwards, 2009;Gabel & Scheve, 2007;Steenbergen et al, 2007) or trade agreements (Dür & Schlipphak, 2020). Regarding international organizations, Dellmuth and Tallberg (2020a) have also demonstrated that governmental cues may influence citizens' attitudes toward the UN.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another group of researchers focused their attention on political predictors of trade attitudes (Hiscox 2006; Kaltenthaler et al, 2004; Mutz, 2017; Medrano & Braun, 2012; Winslett, 2016; Dür & Schlipphak, 2020). Among them, some argue for the importance of partisanship in shaping one’s trade opinion (Mutz, 2017), while others investigate the effects of framing and endorsement (Hiscox, 2006; Medrano & Braun, 2012) or the relationship between trade opinion and party competition (Winslett, 2016).…”
Section: Determinants Of Trade Opinionmentioning
confidence: 99%
“…Additionally, Hiscox (2006) finds that less educated respondents are more sensitive to the framing effect, and endorsement can raise support for trade across the board especially among those who received anti-trade framing. Using a survey experiment, Dür and Schlipphak (2020) only find limited evidence for elite cueing effects on citizens’ support for the Transatlantic Trade and Investment Partnership (TTIP) in both Germany and Spain, but they argue that the elite cueing effects are likely understated because of participants’ possible exposure to elite cues outside the context of the experiment. Other research on trade opinion suggests that the general public is less likely than elites to support free trade (Herrmann et al, 2001), and that parties do change their approach to trade policy depending on the distribution of public opinion in the electorate (Winslett, 2016).…”
Section: Determinants Of Trade Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our validation study, we collected data from four nationally representative samples (Ntotal = 8,310, Nclean = 6,461). 9 Sample 2A was a US representative sample (N = 3,692) with interlocking age and gender quota (i.e., each category contains a representative relative proportion of the other category) accessed through Respondi, an ISO-certified international organization for market and social science research (for previous applications see e.g., Dür & Schlipphak, 2021;Heinsohn et al, 2019;Roozenbeek, Freeman, et al, 2021).…”
Section: Participantsmentioning
confidence: 99%